2017
DOI: 10.5863/1551-6776-22.3.176
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoids in Pediatrics

Abstract: Despite its controversial nature, the use of medical marijuana and cannabis-derived medicinal products grows more popular with each passing year. As of November 2016, over 40 states have passed legislation regarding the use of either medical marijuana or cannabidiol products. Many providers have started encountering patients experimenting with cannabis products for a wide range of conditions. While the debate continues regarding these agents for both medicinal and recreational use in the general population, sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 28 publications
0
25
0
4
Order By: Relevance
“…Moreover, CBD is anti-emetic [47], has antitumoral properties against many types of cancer [48] and is also suggested to have antipsychotic, anxiolytic and antidepressant effects [49]. Finally, as already mentioned above, numerous studies have shown CBD to have anticonvulsive properties [50].…”
Section: Therapeutic Uses and Mechanisms Of Action Of Cbdmentioning
confidence: 99%
“…Moreover, CBD is anti-emetic [47], has antitumoral properties against many types of cancer [48] and is also suggested to have antipsychotic, anxiolytic and antidepressant effects [49]. Finally, as already mentioned above, numerous studies have shown CBD to have anticonvulsive properties [50].…”
Section: Therapeutic Uses and Mechanisms Of Action Of Cbdmentioning
confidence: 99%
“…Reports by neurologists of the Victorian Epoch concerning the use of cannabis in the treatment of epilepsy were promising [55]. However, when phenobarbital and phenytoin were introduced to the market, the use of products based on marijuana decreased [56].…”
Section: Epilepsymentioning
confidence: 99%
“…Neural mechanisms by which CBD may influence mood and behaviour are only partially established, but include alterations in neurotransmission and calcium homeostasis, antioxidant activity and anti-inflammatory effects 24. Thus, the endocannabinoid system is a novel target for pharmacological treatments of behavioural problems.…”
Section: Introductionmentioning
confidence: 99%